Increased risk of malignancy in patients aged over 50 with idiopathic inflammatory myositis compared to patients with osteoarthritis of the knee. Issue 5 (2nd September 2020) - Kim, Hyoungyoung; Sung, Yoon-Kyoung; Choi, Seongmi; Im, Seul Gi; Jung, Sun-Young; Jang, Eun Jin; Yoo, Dae Hyun; Cho, Soo-Kyung
Abstract: Objectives: To estimate risk of malignancy in patients with idiopathic inflammatory myositis (IIM) compared to patients with knee osteoarthritis (OA). Methods: Patients with IIM and knee OA aged over 50, who had no history of malignancy, were identified using Korean National claims database from January 2012 to December 2014. They had been observed until a malignancy was diagnosed or up to the end of the study, December 2015. The incidence rate (IR) of malignancy in IIM patients was calculated and compared with knee OA patients using standardized incidence ratio (SIR). Results: A total of 634 polymyositis (PM) and 556 dermatomyositis (DM) patients were included. Overall, 100 solid (IR 270.4/10, 000 person-years (PY), 95% confidence interval (CI) 217.4–323.4) and 12 hematologic malignancies (IR 32.4/10, 000 PY, 95% CI 14.1–50.8) occurred. Compared with knee OA, risk of overall (SIR 1.5, 95% CI 1.2–1.8), solid (SIR 1.4, 95% CI 1.1–1.6), and hematologic malignancy (SIR 5.7, 95% CI 2.5–9.0) were increased in IIM patients. This was due to increased incidence of malignancy in DM (hematologic malignancy, SIR 8.7, 95% CI 2.7–14.7, solid malignancy, SIR 1.5, 95% CI 1.1–1.9). Conclusion: Patients with IIM, especially DM, have an increased risk of malignancy compared to patients with knee OA.